Rehabilitation strategies for post-surgical head and neck cancer patients: A physiotherapist’s perspective - Sheeba Kauser, Mohammed; Karmakar, Subhasis (IP Indian Journal of Anatomy and Surgery of Head Neck and Brain, 2025)
Head and neck cancer (HNC) and its associated treatments, including surgery, radiation, and chemotherapy, can result in significant physical and functional impairments. Post-surgical rehabilitation plays a crucial role in restoring functional independence, managing symptoms, and improving overall quality of life for these patients. Physiotherapists are integral to the multidisciplinary approach required for HNC rehabilitation, focusing on improving mobility, managing pain, optimizing respiratory and swallowing function, and addressing psychosocial well-being. This article explores key rehabilitation strategies from a physiotherapist's perspective for post-surgical HNC patients.